Alzheimer’s disease and depression in the elderly: A trajectory linking gut microbiota and serotonin signaling - Cutuli, Debora; Giacovazzo, Giacomo; Decandia, Davide; Coccurello, Roberto (Frontiers in Psychiatry, 2022)
The occurrence of neuropsychiatric symptoms in the elderly are viewed as an early signature of subsequent cognitive deterioration and conversion from mild cognitive impairment to Alzheimer’s disease. Moreover, the prognosis of both severity and progression of clinical dementia is generally aggravated by the comorbidity of neuropsychiatric symptoms and decline in cognitive function. Undeniably, aging and in particular unhealthy aging, is a silent “engine of neuropathology” over which multiple changes took place, including drastic alterations of gut microbial ecosystem. Thus, this narrative review evaluates the role of gut microbiota changes as possible unifying concept through which the comorbidity of neuropsychiatric symptoms and Alzheimer’s disease can be considered. However, not the entire spectrum of neuropsychiatric symptoms may be associated to the same type of alterations of bacteria population found in patients with Alzheimer’s disease, nor the highly heterogenous group of neuropsychiatric drugs may produce similar changes of gut bacterial diversity. A very intriguing exception seems that of depression, which is one of the most frequent neuropsychiatric symptoms in dementia and a mood disorder frequently associated with brain aging. Antidepressants (i.e., serotonin reuptake inhibitors) or tryptophan dietary supplementation have been shown to reduce Amyloid β-loading, reinstate microbial diversity and reduce abundance of bacterial taxa dominant in depression and Alzheimer’s disease. Hence, the review will briefly examine the trajectory passing through dysfunction of gut microbiota composition, selected bacterial taxa, and alteration of tryptophan and serotonin metabolism/neurotransmission as overlapping mechanisms in common between depression, Alzheimer’s disease and unhealthy aging.